Review of variants of uncertain significance in hypertrophic cardiomyopathy: a single-center multi-ethnic population experience - BK Bui, Khiong Chung; Hwei Sung, Ling; Y. Y., Oon; Yee Ling, Cham; L. H, Ngu; I. X., Pang; Francis Eng Pbeng, Shu; C. T., Tan; K. T., Koh; Asri, Said; Alan Yean Yip, Fong; T. K., Ong (European Society of Cardiology, 2025)
Background: Genetic testing is recommended by international guidelines for patients with hypertrophic cardiomyopathy (HCM). It is particularly valuable for relatives who may benefit from predictive testing to assess their risk of developing HCM. Identifying likely pathogenic or pathogenic variants in genes associated with HCM enhances diagnostic confidence. However, variants of uncertain significance (VUSs) pose significant challenges for clinical counseling and management due to their unclear impact on health, limiting the clinical utility of genetic testing. Purpose: This study aimed to investigate the incidence of VUSs in HCM patients and review their characteristics. Methods: A retrospective analysis was conducted on VUSs identified in genes associated with HCM at the cardiogenetics clinic of single heart centre from 2020 to 2024. Results: Among 30 patients with a confirmed or suspected diagnosis of HCM who underwent genetic testing, the findings included: 1 case turn out to be genocopies- PRKAG2 syndrome, 6 patients with negative genetic findings, 5 patients with pathogenic variants identified, (TNNT2, TNNI3, MYL2, MYH7, ALPK3). VUSs were identified in 17 patients (58%), with some exhibiting polygenic patterns (2-3 variants per patient). A total of 22 distinct VUSs were identified, involving the following genes:MYOM1, CALR3, BAG3, LDB3, MYH7, ALPK3, JPH2, MYLK2, FLNC, MYH6, TCAP, MYBPC3, VCL, NEBL, and PDLIM3. Conclusion: The high incidence of VUSs in HCM patients highlights the need for further evaluation of genetic findings to improve risk stratification and the identification of family members at elevated risk. Continued reclassification efforts and enhanced genetic analysis techniques may enhance the clinical relevance of genetic testing for HCM.